Cardiac cachexia: hic et nunc: "hic et nunc" — here and now. (15th December 2015) - Loncar, Goran; Springer, Jochen; Anker, Markus; Doehner, Wolfram; Lainscak, Mitja
Abstract: Cardiac cachexia (CC) is the clinical entity at the end of chronic natural course of heart failure (HF). Despite the efforts, even the most recent definition of cardiac cachexia has been challenged, more precisely the addition of new criteria on top of obligatory weight loss. The pathophysiology of CC is complex and multifactorial. Better understanding of pathophysiological pathways in body wasting will contribute to establish potentially novel treatment strategies. The complex biochemical network related with CC and HF pathophysiology underlines that a single biomarker cannot reflect all of the features of the disease. Biomarkers that could pick-up the changes in body composition before they convey into clinical manifestations of CC would be of great importance. The development of preventive and therapeutic strategies against cachexia, sarcopenia and wasting disorders is perceived as an urgent need by healthcare professionals. The treatment of body wasting remains an unresolved challenge to this day. As CC is a multifactorial disorder, it is unlikely that any single agent will be completely effective in treating this condition. Among all investigated therapeutic strategies, aerobic exercise training in HF patients is the most proved to counteract skeletal muscle wasting and is recommended by treatment guidelines for HF. Highlights: epidemiological data about prevalence of cardiac cachexia remain scarce patophysiology of cardiac cachexia is complex and multifactorial diagnostic and prognostic biomarkers are under investigation in cardiac cachexia no evidence based strategy for cachexia available but many interventions in clinical trials